Case Report: A heterozygous mutation of NLRP3 in a Chinese child with NLRP3-AID - Ruan, Yangming; Ge, Ting; Wang, Yizhong; Zhang, Ting; Song, Feifei (Frontiers in Pediatrics, 2025)
BackgroundNLR family pyrin domain containing 3 (NLRP3)–associated autoinflammatory disease (NLRP3-AID), formerly known as cryopyrin-associated periodic syndrome, is a group of AIDs comprising neonatal-onset multisystem inflammatory disorder, Muckle–Wells syndrome, and familial cold autoinflammatory syndrome. Mutations in the NLRP3 gene are considered central to its pathogenesis.Case reportHere, we present a Chinese infant diagnosed with severe NLRP3-AID who carried a heterozygous variant in the NLRP3 gene. The patient exhibited recurrent episodes of fever, urticaria-like rashes, aseptic meningitis, and hearing loss. During hospitalization, elevated inflammatory markers and leukocytosis in body fluids were observed without evidence of infection. DNA sequencing identified a de novo heterozygous mutation, c.1006A > G (p.I336V), in the NLRP3 gene.ConclusionWe report an infant with NLRP3-AID and emphasize the importance of early diagnosis based on clinical manifestations.